Corporate social responsibility as an indicator for employer attractiveness : a cross-cultural study - Nils Schweers 1988- (2015)
This Thesis is dedicated to research if CSR (Corporate Social Responsibility) activities that are undertaken by companies can affect the attractiveness of those companies as a potential employer. Appreciating the fact that the underlying conceptualization of CSR can differ in a cultural context, this study is carried out as a cross-cultural study, re-searching also the effects of different cultural backgrounds on perceiving CSR activities as an important characteristic for a potential employer. The target group of this study will be graduate business students. The main objective of this study is therefore to research whether CSR activities of companies can function as an attractiveness factor from a graduate business student's perspective. Furthermore, the study aims to identify the underlying set of values that determine the perceived importance of CSR. The purpose of this study is one the one hand to research the correlation of CSR activities and company attractiveness which can be beneficial for the Human Resource Management as an instrument for attracting talent and on the other hand to provide evi-dence on the connection between different sets of values and the perceived importance of CSR. The study will be conducted by gathering a set of primary data through a survey. The data set will consist of responses by participants who are graduate business students from India, Iceland, Germany and USA. Key Words: CSR, Corporate Social Responsibility, P-O fit, cross-cultural differences, individual values, cultural dimensions